Le maïs et la mémoire bioculturelle de Mésoamérique - Víctor M. Toledo; Narciso Barrera-Bassols (Revue d'ethnoécologie)
Our contribution focuses on revisiting the theme of maize and the regenerative traditional agricultural system called milpa (corn-beans-squash) in its cosmogonic, cognitive, and practical context within the Mesoamerican agricultural tradition. The milpa crop fields are seen as a historical and current result of ten thousand years of civilization during which biocultural efforts have been revolving around agriculture. This extensive territory where maize – which today constitutes the staple food in Mexican and Central American kitchens – finds its origin has become a symbolic point of reference, forming the core nucleus of a cosmic matrix. Growing maize has unceasingly sculpted heterogeneous landscapes, providing meaning to the systems of knowledge about non-human living beings and their intricate cycles. The study of a Purhépecha community from Central Mexico, focusing on the study of their way of thinking and knowledge associated with maize cultivation practices, demonstrates the biocultural existence, adaptation, and resilience of this sacred-plant. It also reveals the meanings it acquires within the complex interpretation of its multiple relationships with other life entities within the community’s ontology. Through an ethnoecological approach, this example - along with many others - reveals the inseparable relationships between existing beings from the Mesoamerican world (Kosmos), the cognitive systems that organize reality (Corpus), and practices resulting from a thousand-year-old experience surrounding corn cultivation (Praxis). This active and concentrated biocultural memory belongs to the peoples who are made of maize.